UV-crosslinked Polymeric Materials for Encapsulation of ZnO Nanowires in Piezoelectric Fingerprint Sensors. (2016) - Bouvet-Marchand, A.; Loubat, M.; Graillot, A.; Volk, J.; Dauksevicius, R.; Saoutieff, E.; Viana, A.; Christian, B.; Lebedev, V.; Sturm, C.; Loubat, C.
Abstract: The work presented here describes new UV-crosslinkable thin layer polymeric materials for the encapsulation of ZnO nanowires (NWs) in multi-NWs pressure based fingerprint sensors. Such innovative sensor is a novel technology for fingerprint capture developed within the PiezoMAT FP7 European project. The sensing principle is based on the piezoelectric property of ZnO NWs, on which a potential difference is generated when they undergo compression and/or bending forces. Since the pressure induced by the finger cannot be directly applied on the NWs, the deformation is applied through a polymeric material that aims at transferring forces from the finger onto the array of NWs without altering their integrity. Besides, since it is dedicated to be in direct contact with human finger or oil pollutants, the encapsulation layer must also exhibit chemical inertness, as well as hydrophobicity and oleophobicity.